2010
DOI: 10.1097/prs.0b013e3181dbc313
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Silicone Breast Implants by Binding the Antifibrotic Drug Halofuginone Reduces Capsular Fibrosis

Abstract: The results confirmed a decrease in foreign body responses to halofuginone surface-modified silicone implants and mark their potential for obtaining a lessened capsular fibrosis by way of a local antifibrotic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…Whereas during the systemic application of HF partly strong gastrointestinal complaints have been described [39,43]. Recent studies could already elucidate a significant local reduction of the TGF-beta-1-and COL1A1-expression through submuscular implantation of a HF coated silicone implant [44]. The present study demonstrates that the local effect of HF is not only limited on TGF-beta-1 and collagen-I, but also affects the pro-angiogenic factors bFGF and MMP-2, however not MMP-9.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas during the systemic application of HF partly strong gastrointestinal complaints have been described [39,43]. Recent studies could already elucidate a significant local reduction of the TGF-beta-1-and COL1A1-expression through submuscular implantation of a HF coated silicone implant [44]. The present study demonstrates that the local effect of HF is not only limited on TGF-beta-1 and collagen-I, but also affects the pro-angiogenic factors bFGF and MMP-2, however not MMP-9.…”
Section: Discussionmentioning
confidence: 98%
“…To examine the effects of montelukast in reducing the occurrence of capsular contracture, we histopathologically examined the thickness of the capsule and the number of inflammatory cells. Philip et al [21] performed an experimental study to examine the effects of reducing the occurrence of capsular fibrosis, according to which, of various quantitative factors indicating the degree of the formation of myofibroblasts that are the factors most responsible for the occurrence of capsular contracture, TGF-β (one of the key cytokines that are involved in the cellular growth and differentiation and the synthesis of extracellular matrix) has been identified as the most important substance. Thus, by provoking the occurrence of the chronic inflammations, it causes the formation of granulation tissue and fibrosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14 It has been demonstrated that Halofuginone reduces fibrosis formation in many pathological conditions. 8,[13][14][15][16][17][18][19] Previously Halofuginone has shown to reduce fibrosis in mice models with stretched skin due to scleroderma 20 , to decrease in the liver fibrosis model due to thiacetamide 21 , to lessen graft versus host disease 22 , to improve muscular dystrophies including dysferlinopathy 19,23 , and lessen mesangial cell proliferation and matrix deposition in the kidney. 24 By the light of these studies, we hypothesized that Halofuginone may be able to ameliorate radiation-induced cardiovascular injury.…”
Section: Discussionmentioning
confidence: 99%